Teaching English in Junior High School in Southern Thailand: Challenges Experienced by Pre-service Indonesian Teachers - Lutvia Lutvia; Khusnul Khatimah; Rani Herning Puspita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study investigated the obstacles faced by Indonesian pre-service English teachers during their teaching practicum and the underlying causes at junior high schools in Southern Thailand. Semi-structured interviews were conducted with three Indonesian pre-service English teachers undertaking their practicum at junior high schools in Southern Thailand to gather qualitative case study data. Six interconnected categories of issues exist: linguistic barriers (students' restricted vocabulary and pronunciation difficulties stemming from Thai, Malay, and Patani Malay); communication barriers (language disparities and dependence on translation); psychological barriers (students' apprehension regarding errors); and classroom engagement challenges (disinterest and diminished focus due to multilingual cognitive processes). Five contributing factors included restricted English exposure beyond the classroom, first language influence resulting in phonological interference, a curriculum-proficiency mismatch leading to systemic barriers, monotonous teacher-centered methodologies with insufficient learning media, and structural constraints such as time and facilities. Southern Thailand possesses a multitude of languages, rendering it distinctive within Thai EFL. Students were required to attain proficiency in Thai, Malay, Patani Malay, and Arabic before acquiring English as a fifth language. The results indicated that challenges in multilingual education are systemic, necessitating context-specific pedagogical approaches, enhanced training for novice educators, curriculum modifications to align with students' proficiency levels, and improved institutional support for junior high school teaching, including time and technological resources. Keywords: English Teaching Challenges, Pre-service Teachers, Southern Thailand